Safety and efficacy of treatment with lumacaftor in combination with ivacaftor in younger patients with cystic fibrosis. (4th May 2019) - Cheng, Pi Chun; Alexiou, Stamatia; Rubenstein, Ronald C.
ABSTRACT: Introduction : Cystic fibrosis (CF) is the most common autosomal recessive disorder among Caucasians affecting ~70, 000 people worldwide. The lack of functional cystic fibrosis transmembrane conductance regulator (CFTR) causes dysregulation of epithelial fluid transport in the lungs, gastrointestinal tract, and sweat glands. Areas covered : The most common disease-causing CFTR mutation, F508del, is present in over 75% of those affected;. therapies targeting F508del function have the promise to reduce morbidity and mortality in the majority of patients with CF. The combination of lumacaftor, which corrects the aberrant intracellular trafficking of F508del, and ivacaftor, which potentiates CFTR function, is known as Orkambi TM, and is the first drug approved for the treatment of CF in patients who are F508del-homozygotes. Orkambi TM is currently approved for use in children aged 2 and older based on recent data from open-label Phase 3 clinical safety studies. Expert opinion : Orkambi TM modestly improves clinical outcomes for people with CF who are F508del-homozygotes, and does so with a reasonable safety profile. This is a major advance in therapy for CF, but further advances are needed, perhaps with the addition of a third agent to this combination small molecule therapy, in order to expand both the targeted population and beneficial effects.